Promotion of normal healing of bone defects under estrogen deficiency by implantation of beta‐tricalcium phosphate composed of rod‐shaped particles. Issue 2 (6th November 2013) - Tatsukawa, Eri; Gonda, Yoshinori; Kamitakahara, Masanobu; Matsuura, Masaaki; Ushijima, Masaru; Shibata, Yasuaki; Yonezawa, Ikuho; Fujiwara, Mutsunori; Ioku, Koji; Ikeda, Tohru
ABSTRACT We compared the healing of bone defects in ovariectomized rats implanted with beta‐tricalcium phosphate (β‐TCP) composed of rod‐shaped particles, which were prepared using the applied hydrothermal method (HTCP), and that of bone defects implanted with conventional β‐TCP composed of globular‐shaped particles (CTCP), which were prepared by normal sintering. Eight‐week‐old female Wistar rats were ovariectomized, and 2 weeks after the operation, 0.5‐ to 0.6‐mm diameter spherical granules of each ceramic were implanted in a bone defect created in the distal end of the femur. Four, 8, and 12 weeks after implantation, the amount of newly formed bone implanted with HTCP was significantly larger than that implanted with CTCP and was equivalent to that in non‐ovariectomized sham‐operated rats. Without implantation, spontaneous repair of the trabecular bone was barely observed. The physiological structure of the trabecular network was maintained in the region implanted with HTCP, but that in the region implanted with CTCP was severely destroyed. Gene expression microarray analysis revealed that the expression of genes involved in interferon signaling pathways was upregulated in osteoclasts cultured on HTCP compared with that cultured on CTCP. Our results suggest that the microstructure of β‐TCP affected the biological behavior of osteoclasts and regulated local bone metabolism. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:189–196, 2014.